Synthesis of Disperse Dyes from Pyridone and Resorcinol Coupled to Diazotized 2-Amino-4-chloro-5-formylthiazole and Application to Polyester. (17th July 2014) - Lams, Yusuf Y.; Nkeonye, P. O.; Bello, K. A.; Yakubu, M. K.; Lawal, A. O.
Abstract : The aim of this study was to synthesize disperse dyes in the derivative of 2-amino-4-chloro-5-formylthiazole by conventional diazotization and couplings with pyridone and resorcinol. The dyes were characterized by visible absorption spectroscopy, IR spectral studies, and 1 H and 13 C NMR. The pyridone and resorcinol substituted dyes exhausted well with good depth on 100% polyester fabrics with a shade of brown and purple colours, respectively. The heteroatom and the intrinsic conjugation in the thiazole structure results in high bathochromic shifts and lead to brightness of shades. The dyed fabrics showed very good to excellent wash fastness and moderate to good light and perspiration fastness properties.